Carcinoma de células escamosas de grandes proporções - Gaetti Jardim, Ellen Cristina [UNESP]; Pereira, Cassiano Costa Silva [UNESP]; Guastaldi, Fernando Pozzo Semeghini [UNESP]; Shinohara, Élio Hitoshi [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (My University, 2010)
The oral and oropharyngeal cancer is aggressive and, in Brazil, the incidence is considered one of the world’s tallest, the most common of head and neck. It affects males more intensively and 70% of cases are in adults over 50 years of age. It is located usually on the floor of the mouth and tongue. Therefore, the purpose of this study is to report a case of male patient, 78 years of age, leukoderma who sought hospital care. Reported frequent smoking and alcoholism. On physical examination headgear, there was the presence of lymph node fixed, painless 1.5 to 2 cm in diameter in the submandibular region. Physical examination intraoral ulcer was found at about 5 cm at its greatest extent, localized to the left oral floor region of the oropharynx, reddish, hardened edges, surface and bottom corrugated carton. The differential diagnosis suggested was traumatic ulcer, paracoccidioidomycosis and squamous cell carcinoma. The approach employed was obtained by incisional biopsy and the piece sent to histopathological analysis, confirming the case of squamous cell carcinoma. The treatment consisted in clarifying the patient about the disease and the need to search for an oncology center. It is concluded that the oral clinical examination is accurate in all major injuries to mouth, even if the chief complaint does not focus on this. In individuals at high risk examination should be systematic and individuals with suspicious lesions should be referred to specialist consultation.

O câncer de boca e orofaringe é de comportamento agressivo e, no Brasil, a incidência é considerada uma das mais altas do mundo, sendo o mais comum da região de cabeça e pescoço. Acomete o gênero masculino de forma mais intensa e 70% dos casos são em indivíduos acima dos 50 anos de idade. Localiza-se, geralmente, em assoalho da boca e língua. Diante disso, o objetivo deste estudo é relatar um caso clínico de paciente do gênero masculino, 78 anos de idade, leucoderma que procurou atendimento hospitalar. Relatou fumo e alcoolismo freqüente. No exame físico extrabucal, verificou-se a presença de nódulo linfático fixo, indolor de 1,5 a 2cm de diâmetro em região submandibular. Ao exame físico intrabucal constatou-se lesão ulcerada com cerca de 5 cm em sua maior extensão, localizada de assoalho bucal esquerdo até a região de orofaringe, coloração avermelhada, bordas endurecidas, superfície corrugada e base cartonada. O diagnóstico diferencial sugerido foi úlcera traumática, paracoccidioidomicose e carcinoma de células escamosas. A conduta realizada foi biópsia incisional e a peça obtida enviada à análise histopatológica, confirmando se tratar de carcinoma de células escamosas. O tratamento consistiu no esclarecimento do paciente a cerca da doença e da necessidade de procura por um centro de oncologia. Conclui-se que o exame clínico bucal acurado é importante em todas as lesões em boca, mesmo que a queixa principal não se concentre nesta. Nos indivíduos de maior risco o exame deve ser sistemático e indivíduos com lesões suspeitas devem ser encaminhados à consulta especializada.
Mous cell carcinoma of large dimensions
Keywords: Pathology; Diagnosis; Squamous cell carcinoma; Patologia; Diagnóstico; Carcinoma de células escamosas